Narrow-band single-photon emission through selective aryl functionalization of zigzag carbon nanotubes. Issue 11 (November 2018) - Saha, Avishek; Gifford, Brendan; He, Xiaowei; Ao, Geyou; Zheng, Ming; Kataura, Hiromichi; Htoon, Han; Kilina, Svetlana; Tretiak, Sergei; Doorn, Stephen
Abstract The introduction ofsp 3 defects into single-walled carbon nanotubes through covalent functionalization can generate new light-emitting states and thus dramatically expand their optical functionality. This may open up routes to enhanced imaging, photon upconversion, and room-temperature single-photon emission at telecom wavelengths. However, a significant challenge in harnessing this potential is that the nominally simple reaction chemistry of nanotube functionalization introduces a broad diversity of emitting states. Precisely defining a narrow band of emission energies necessitates constraining these states, which requires extreme selectivity in molecular binding configuration on the nanotube surface. We show here that such selectivity can be obtained through aryl functionalization of so-called 'zigzag' nanotube structures to achieve a threefold narrowing in emission bandwidth. Accompanying density functional theory modelling reveals that, because of the associated structural symmetry, the defect states become degenerate, thus limiting emission energies to a single narrow band. We show that this behaviour can only result from a predominant selectivity forortho binding configurations of the aryl groups on the nanotube lattice. Aryl functionalization of carbon nanotubes generatessp 3 defects capable of quantum light emission. A multiplicity of possible binding configurations, however, leads to spectrally diverse emission bands. Now, it is shown that the structural symmetry of zigzag nanotubes and a high chemical selectivity forortho configurations results in defect-state emission from a single narrow band.